Applications of artificial intelligence-powered prenatal diagnosis for congenital heart disease - Liu, Xiangyu; Zhang, Yingying; Zhu, Haogang; Jia, Bosen; Wang, Jingyi; He, Yihua; Zhang, Hongjia (Frontiers in Cardiovascular Medicine, 2024)
The AI-powered analysis methods of medical images and clinical records can now match the abilities of clinical physicians. Due to the challenges posed by the unique group of fetuses and the dynamic organ of the heart, research into the application of AI in the prenatal diagnosis of congenital heart disease (CHD) is particularly active. In this review, we discuss the clinical questions and research methods involved in using AI to address prenatal diagnosis of CHD, including imaging, genetic diagnosis, and risk prediction. Representative examples are provided for each method discussed. Finally, we discuss the current limitations of AI in prenatal diagnosis of CHD, namely Volatility, Insufficiency and Independence (VII), and propose possible solutions.